2022
DOI: 10.1093/jscr/rjac073
|View full text |Cite
|
Sign up to set email alerts
|

Pectointercostal fascial plane block for rescue pain management of traumatic sternal fracture following inadequate thoracic epidural block: a case report

Abstract: Adequate pain control after multisystem trauma including the chest wall is essential for improved patient outcomes, especially with sternum and rib fractures. The thoracic epidural is considered the gold standard in pain management of thoracic injury; however, failure or patchy epidural is not uncommon. Pectointercostal fascial plane block (PIFB) is regularly used in cardiac surgery to provide analgesia to the anterior chest wall; however, there are few reports of PIFB being used as a primary block for the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…These findings align with the results reported by Zhang et al (26,27) and Thomas et al (32). Pecto-intercostal fascial plane block has also been successfully employed for rescue analgesia in a patient who had extensive chest wall trauma and a sternal body fracture following an inadequate thoracic epidural block, resulting in marked improvement in ventilatory function (33). Additionally, it has been used to manage pain and facilitate weaning in a critically ill patient with retractable ribcage pain at the site of endothoracic drainage (34).…”
Section: Discussionsupporting
confidence: 89%
“…These findings align with the results reported by Zhang et al (26,27) and Thomas et al (32). Pecto-intercostal fascial plane block has also been successfully employed for rescue analgesia in a patient who had extensive chest wall trauma and a sternal body fracture following an inadequate thoracic epidural block, resulting in marked improvement in ventilatory function (33). Additionally, it has been used to manage pain and facilitate weaning in a critically ill patient with retractable ribcage pain at the site of endothoracic drainage (34).…”
Section: Discussionsupporting
confidence: 89%
“…Our case demonstrates that sternum surgery can be performed without general anesthesia, even in a patient with a traumatic sternal fracture, by implementing a bi-level, bilateral US-guided S-PIP block under sedation. US-guided S-PIP block was used for rescue pain management of traumatic sternal fracture [4] and rib cage pain in ICU patients [5]. Karapinar YE et al [6] have recently reported awake sternum revision with US-guided transverse thoracic muscle plane block, which is similar to our case.…”
Section: Discussionsupporting
confidence: 80%